Performance comparisons of selected protection algorithms for optical networks - Chowdhury, Sadrul Habib (University of Ottawa (Canada), 2009)
Optical networking is a promising solution to support the ever increasing Internet traffic. This thesis aims to investigate the important issue of network protection after a failure occurs in the network. We propose a framework for measuring the performances of network protection algorithms for various protection metrics. The framework is designed to easily and quickly collect protection measures for an algorithm that can be effectively compared to the same protection measure of another algorithm. We then use this framework to compute and compare the performances of various network protection algorithms, mainly between algorithms that use p-cycles and ones that use protection trees. Different performance measures including restorability, sharability and change in data-path length are used. We use the framework on randomly generated mesh networks with varying topology parameters such as network size, network order, average nodal degree etc. We use the result to study the effect of the variation in different network parameters on the performances of the protection algorithms. Finally, commercial networks are used as specific application examples.
Keywords: Computer Science.